1992
DOI: 10.2337/diacare.15.5.657
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia in Different Degrees of Glucose Intolerance in a Finnish Population-Based Study

Abstract: Hypertriglyceridemia is common in subjects with NIDDM and IGT and is often associated with low HDL cholesterol, high total cholesterol, hyperinsulinemia, and elevated serum uric acid concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…1,4 The prevalence of hypertriglyceridemia is three times higher in men with type 2 diabetes compared to men with normal glucose tolerance, 28 and high total and VLDL triglycerides are independent and powerful predictors of CHD in type 2 diabetes. 4,5 Indeed, type 2 diabetic patients with serum triglycerides above 2.3 mmolal have a 2-fold increased risk of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 The prevalence of hypertriglyceridemia is three times higher in men with type 2 diabetes compared to men with normal glucose tolerance, 28 and high total and VLDL triglycerides are independent and powerful predictors of CHD in type 2 diabetes. 4,5 Indeed, type 2 diabetic patients with serum triglycerides above 2.3 mmolal have a 2-fold increased risk of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The partial correlations of Fig 6 suggest that metabolic factors associated with insulin resistance and elevated triglycerides could mediate in part the reduction in HDL 2b associated with adiposity. Salomma et al [40] have hypothesized the primacy of insulin resistance in mediating associations between adiposity and lipoproteins in men. Taskinen et al [41] reported that insulin therapy increases HDL 2 and reduces HDL 3 concomitant to a twofold increase in adipose tissue lipoprotein lipase activity.…”
Section: Insulinemia and Adipositymentioning
confidence: 99%
“…5,8 Higher TG is also a feature of prediabetic subjects. [12][13][14][15][16] Insulin resistance and/or B-cell failure in prediabetic and diabetic subjects may be responsible for higher TG in these subjects. Studied in FDRs have shown raised TG 9,10 and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…11 But there are very limited studies to find lipid abnormalities in each prediabetic groups. High level of TG was found in IFG, IGT, IFG-IGT, [12][13][14][15][16] and low HDL in IFG and IGT. [13][14][15] Probably insulin resistance and/or secretion defect in these subjects have role for this dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%